The Effect of Taxpayer Awareness and Tax Knowledge on Tax Compliance in Nepal - Bhattarai, Toya Nath; Khadka, Ajaya Kumar; Joshi, Ramesh Datta (NCC Journal, 2025)
This research paper examines the impact of taxpayer knowledge and awareness on tax compliance within the framework of Nepal's changing taxation system. A total of 384 taxpayers registered in Kathmandu Valley were selected for the study, which utilized a descriptive and explanatory methodology. The researcher gathered data using a structured questionnaire and analyzed it using linear regression. The results show that an individual's tax knowledge (r=0.482, p<0.001) and taxpayer awareness (r=0.618, p<0.001) significantly influence tax compliance. The interaction of these two variables on tax compliance behaviour accounts for 42.4% (R² = 0.424, F (2, 381)= 140.10, p<0.001), with tax awareness being the more significant factor. The results underscore the significance of education and transparency in fostering voluntary compliance. Nepal's government must enhance its taxpayer education initiatives and digital services to increase legal compliance among citizens.